Políticas de cobranza y su incidencia en la recaudación de tributos por parte del servicio de rentas internas (sri) de la Provincia de Cotopaxi, Cantón Latacunga durante el primer trimestre de los años 2017-2018 - Chaluisa Comina, Vilma Estefanía (2019)
The present research work fulfills the purpose of analyzing, collection policies and its incidence in the collection of taxes by the Internal Revenue Service of Cotopaxi Province, Canton Latacunga during the first quarter of years 2017-2018, seeking to promote improvement of tax collection processes by comparing the collected amounts maintained by the institution, through generated figures quarterly and in turn observing the incidence of collection policies and strategies within the framework of persuasion for the payment of taxes debts of taxpayers. Within the proposed research, a methodology with a quantitative approach was used, since levels of collection and comparison of two quarters of different years were established, descriptive because it allowed us to know the procedures and strategies used and at the same time explanatory because by this can measure the incidence collection maintained by the SRI, with the application of techniques such as interviews and surveys applied to 328 natural persons. The results show positive effects of the collection policies of the Internal Revenue Service Cotopaxi in the taxes collection for first quarter period 2017-2018 years.